Development of Steam Innovation Learning Against Conventional Methods of Teachers in Islamic Boarding Schools - Icon Herawati; Sugeng Widodo; Herpratiwi Herpratiwi; Muhammad Nurwahidin (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The presence of information and communication technology does not escape the impact on the education system in Indonesia, especially in learning and learning, the presence of technology in the field of education has an impact on the convenience in the process of delivering learning to know from teacher centered to student centered learning, of course by utilizing information and communication technology media, students and teachers can find learning resources and references very easily through information and communication technology media. The style of pesantren life can be seen from the structure of the teaching provided. From the structure and systematics of the teaching, you will find repeated levels from one level to another without seeing the end. The issues taught are often discussions that have been repeated over a period of years, although the textbooks used are different. It starts with a small book (mabsuthÃ¢t) containing simple, concise texts, then moves to a medium book level (mutawassith). The lessons are given in recitations that take the form of open lectures, where the kiai reads, translates and explains the issues mentioned in the text being studied. Therefore, in order to solve the problem of learning methods, a new breakthrough in learning is needed. This research aims to describe the literature on steam innovation learning approaches to conventionoal methods in Islamic boarding schools. This study is a research and development study using a mixed approach (Mixed Method) which aims to determine the effectiveness of the development of steam innovation learning training on conventional methods of teachers in boarding schools. By using the ADDIE model, analysis, design, development, implementation and evaluation. This research was conducted at Ponpes Darul Huffaz Pesawaran, the sample of this study amounted to 30 teachers. The research technique used interviews, observation, documentation and assessment instruments. As well as data analysis using quantitative data from pretest and posttest scores which are then tested using the N-Gain statistical formula. By adopting the STEAM innovation learning approach, boarding schools can provide teachers with the skills needed in the future. In addition, this approach can also help teachers to develop creativity, critical thinking, and problem solving, which can help them in everyday life and the future. overall total results with an average of 0.75 with a high classification as well as the effective effectiveness level of STEAM innovation learning development training against conventional methods of teachers at Darul Huffaz Pesawaran boarding school.